Novel strategies for assessing platelet reactivity - Algahtani, Mohammad; Heptinstall, Stan (Future Medicine, 2017)
There are many approaches to assessing platelet reactivity and many uses for such measurements. Initially, measurements were based on the ability of platelets separated from other blood cells to aggregate together following activation with an appropriate ‘aggregating agent’. Later, measurements of platelet aggregation in blood itself were performed, and this led to a point-of-care approach to platelet function testing. Measurement of secretory activity through the appearance of the activation marker P-selectin on platelets now provides an alternative approach, which enables remote testing. Measurement of vasodilator-stimulated phosphoprotein phosphorylation is also moving toward application in situations remote from the testing laboratory. Here we provide an overview of the various approaches that are now available, assess their advantages and disadvantages, and describe some of the clinical situations in which they are being used.